Public health campaigns and obesity - a critique - Proietto Joseph; Peeters Anna; Walls Helen L; McNeil John J (BMC, 2011)
Abstract Background Controlling obesity has become one of the highest priorities for public health practitioners in developed countries. In the absence of safe, effective and widely accessible high-risk approaches (e.g. drugs and surgery) attention has focussed on community-based approaches and social marketing campaigns as the most appropriate form of intervention. However there is limited evidence in support of substantial effectiveness of such interventions. Discussion To date there is little evidence that community-based interventions and social marketing campaigns specifically targeting obesity provide substantial or lasting benefit. Concerns have been raised about potential negative effects created by a focus of these interventions on body shape and size, and of the associated media targeting of obesity. Summary A more appropriate strategy would be to enact high-level policy and legislative changes to alter the obesogenic environments in which we live by providing incentives for healthy eating and increased levels of physical activity. Research is also needed to improve treatments available for individuals already obese.